Study of Internal Flow with Deceleration in a Cryogenic Chamber Composed of Jet-Type Atomizers - Arriaga, Ian (2025)
The present article delves into the comprehensive study of internal flow dynamics within a cryogenic chamber used for freezing food with high water percent. For cryogenic freezing is necessary to reduce temperature extremely and maintain a uniform distribution, different behaviours may cause structural damages on food. This is because the chamber comprises a circular-sectioned tunnel or chamber coupled with a set of Jet-type atomizers for the injection of liquid nitrogen. The internal flow, predominantly consisting of liquid nitrogen, necessitates prolonged residency within the chamber to uniformly and effectively cool or freeze food traversing its interior. Consequently, the primary aim is to extend the cryogenic fluid's residence time, achieved by strategically decelerating the flow. This deceleration is orchestrated through the strategic injection of the fluid to induce a swirling or vortex effect. The formation of this effect is meticulously executed by positioning the atomizers at periodic intervals around the internal walls of the cylindrical chamber, ensuring a prolonged recirculation of the internal flow. This research endeavour is further augmented by a comprehensive numerical analysis of swirling flow dynamics and associated parameters such as temperature, velocity, pressure and nitrogen-liquid interface. Leveraging the robust capabilities of CFD ANSYS software (Computational Fluid Dynamics), this analysis incorporates sophisticated models including the Volume of Fluid (VOF) model and the k-epsilon turbulence model. Additionally, the construction of a three-dimensional hexahedral mesh, facilitated by ICEM CFD software, adds depth and precision to the numerical simulations. The culmination of this study lies in the profound comprehension of internal flow behaviour and its intrinsic correlation with the design intricacies of the cryogenic system. Variations in nitrogen injection pressures and the strategic deployment of atomizers around the chamber serve as pivotal parameters for elucidating the system's optimal design.